PERAN BISNIS DIGITAL, DESAIN, DAN TEKNOLOGI DI SMK BBC MEDAN - Pasaribu, Widi Sriwahyuni; Aisyah, Charini; Yuandika, Taufik; Hartanto, Denny (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2024)
One of the levels of education in Indonesia is Vocational High School (SMK), whose graduates are expected to be ready to work, especially to create job opportunities according to their vocational skills. Currently, a realistic step that graduates can take is to start a business by leveraging digital technology. Digital business is a transformation toward more efficient business practices. This activity aims to educate students about the role of digital business, design, and technology in entrepreneurship. The partners in this activity are students of SMK BBC Medan. The method used is Community Education as a substitution for science and technology. The material is delivered through lectures with the assistance of PowerPoint. The Community Service Program (PKM) activities include observation, implementation, documentation, and evaluation. The results of the PKM activity observation show that the students have an interest in starting a digital business. This is evident from the enthusiasm and curiosity of the students there.